PERLINDUNGAN KORBAN KEJAHATAN PERDAGANGAN MANUSIA SEBAGAI WUJUD PERLINDUNGAN HAK ASASI MANUSIA - Suryadi, I Gede; Putrawan, Suatra (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014)
This article discussed the protection that can be given to women and children who are victims of human trafficking. Victims of human trafficking are not just for purpose of prostitution or other forms sexual exploitation, but also includes other form of exploitation, such as forced labor, slavery or practices similar to slavery. The government establishes various legislations to provide legal protection for woman and children from becoming victims of human trafficking. The problems faced are : what sort of modus operandi is practiced in human trafficking? And what kinds of legal protection can be given over the victims of human trafficking in terms of human right. The method of this research is normative method. From the result of the research it can be seen that the modus operandi of trafficking is the exploitation and human trafficking occurs to final destination including domestic service, forced marriage and hard labor power with low wages. Legal protection that can be provided is through preventive and repressive efforts undertaken by the government through the community and law enforcement officers.
Keywords: protection, victims, human trafficking, human right